A new species of long-tailed shrew of the genus Sorex (Eulipotyphla: Soricidae) from Sierra de Omoa, Honduras - Andino-Madrid, Alexandra J.; Colindres, Julio E. Mérida; Pérez-Consuegra, Sergio G.; Matson, John O. (Zootaxa, 2020)
The only known species of the genus Sorex in Honduras is Sorex mccarthyi Matson & Ordóñez-Garza, which is endemic to Celaque National Park. This species shows the presence of a postmandibular foramen and canal, a characteristic that is useful to distinguish between species south of the Isthmus of Tehuantepec and unique to the Sorex salvini species group. Recently, two specimens of Sorex were collected in 2018 at Cusuco National Park, northwestern Honduras. These specimens lack the distinctive characteristics possessed by the S. salvini species group and belong to the Sorex veraepacis species group. Previously, the S. veraepacis species group was only known from the highlands of the southern Mexican state of Chiapas and Guatemala. Principal component analysis shows that specimens from Sierra de Omoa are different in size and shape with respect to other known species (i.e., S. veraepacis Alston, S. ibarrai Matson & McCarthy and S. madrensis Matson & Ordóñez-Garza). We describe these two specimens, currently known only from an isolated cloud forest in the Sierra de Omoa, Honduras, as a new species.